Penerapan Manajemen Waktu Pada Pembangunan Basement Proyek 31 Sudirman Suites Makassar - Intan Tangdan; Meti; Josefine Ernestine Latupeirissa (Paulus Civil Engineering Journal, 2023)
Along with the development of the community's need for housing, it has an effect on the rapid development of construction projects in Indonesia, especially in this study, we will discuss apartment housing facilities. The purpose of this research is to understand the obstacles that occur in the basement work of the 31 Sudirman Suites Makassar development project and to analyze alternative scheduling of the basement work of the 31 Sudirman Suites Makassar project using the PERT method. Based on data analysis, it was found that the obstacles that occurred in the basement work of the 31 Sudirman Suites Makassar development project were work delays, changes in job specifications and waiting for confirmation of job specifications from the owner. alternative schedule using the PERT method, obtained a work completion time of 109 weeks while the initial planning time was 115 weeks. Thus scheduling using the PERT method is faster than the initial scheduling plan.